IMÁGENES DEL HOLOCAUSTO. ANÁLISIS DE LA ZONA GRIS Y SU REPRESENTACIÓN EN EL CINE CONTEMPORÁNEO - Elios MENDIETA RODRÍGUEZ (Fonseca, Journal of Communication, 2023)
In his memoirs as an Auschwitz survivor, Primo Levi developed the concept of grey zone to explain the different ways in which the Nazi regime led its Jewish enemy to a process of self-destruction by diffusing the line between victim and executioner. In the aftermath of Auschwitz, this concept quickly spread beyond the limits of the camp and promptly became a necessary piece for the understanding of what happened during the Holocaust, above all due to the accuracy of a concept, grey zone, that still interact with the present.